Gen-Z Consumer Behavior Towards Interest Buy E-Commerce at Majalengka - Mochammad Anjar Albagja (Politeknik Mardira Indonesia, 2024)
This research aims to identify and analyze the influence of trust in using e-commerce, the influence of ease on attitudes towards using e-commerce, the influence of benefits on attitudes towards using e-commerce, and the influence of attitudes on interest in using e-commerce among Generation Z in Majalengka. The research location was conducted in Majalengka. The approach used in this research is quantitative descriptive with the population of Generation Z in Majalengka with a sample size of 20 people using Accidental Sampling technique. The data analysis used is descriptive statistics processed using Excel. The results show that the perception of trust, ease, benefits, and attitudes of Generation Z towards e-commerce buying interest have a positive and significant effect on the increase in consumption patterns of Generation Z towards e-commerce in Majalengka. In its implementation, Generation Z integrates technology into the purchasing interest scheme of e-commerce platforms to provide broad and practical reach.